Design and ethics reflections on practice - Felton, Emma; Zelenko, Oksana; Vaughan, Suzi (Oxon, [England] Routledge, 2012)
"This book presents a multi-disciplinary collection of writing with authors reflecting on design as a process in which ethics and social responsibility are paramount. With contributions from fields as diverse architecture, fashion, urban design, philosophy and education, this book presents innovative ways of thinking about and doing design." -- Publisher
Framing design and ethics Oksana Zelenko and Emma Felton -- Design-ing ethics: the good, the bad and the performative Stephen Loo -- Design, ethics and group myopia Leslie F. Becker -- From allure to ethics: design as a 'creative industry' Justin O'Connor -- Hybridity, hegemony and design in a globalized economy Karen Fiss -- Values and pragmatic action: the challenges of engagement with technical communities in support of value-conscious design Noëmi Manders-Huits and Michael Zimmer -- Designing well: sustain-able interaction design and vegetarianism Gavin Sade -- Design and ethics in digital mental health promotion Oksana Zelenko -- Interaction design, mass communication and the challenge John Hartley -- Living with strangers: urban space, affect and civility Emma Felton -- Built environment, design and ethics: the social responsibility of educational institutions Paul Sanders, Shannon Satherley and Kuniko Shibata -- Rethinking practice: architecture, ecology and ethics Marci Webster-Mannison -- Sustainable housing: family experiences with supply chain ethics Wendy Miller and Laurie Buys -- Fashion, ethics, ethos Paula Dunlop -- Nourishing or polluting: redefining the role of waste in the fashion system Alice Payne -- Looking back, forward and elsewhere: an afterword Tony Fry.
Includes bibliographical references (pages 224-225) and index.
Keywords: Art and morals; Art -- Moral and ethical aspects